Existential Anxiety in the Poetry of Ibn Khafajah Andalusi (450-533 AH): Al Jabal Poem as a model - Al-Ghasini, Zahir; Al-Daoudi, Zaher (Al-Adab Journal, 2022)
This research aims to examine the existential anxiety in Ibn Khafajah Al-Andalusi’s “Al Jabal Poem” (450-533 AH), which is one of the most important poetic pieces in Arabic poetry in general, and in the Andalusian literature in particular. Modern and contemporary critics are still studying its impact. Each critic approaches it from his own critical point of view, which reveals the value of our ancient Arab poetry in the East and West. The Andalusian poets were united with nature, and were able to express its most precise details. Thus, this textual approach aims to approach the Andalusian poetic text, a textual approach that reveals the dimensions of existential anxiety in Andalusian poetry, by taking the poem “Al Jabal” as a text and a subject, relying on the structural approach, and the existential propositions as crystallized by the existential philosophers. Modern critics are studying this phenomenon from different angles: from psychology to anthropology, to semiology, to linguistic and cultural studies, in an attempt to answer the following problematic quesions: What are the most prominent sociocultural influences of anxiety in Ibn Khafajah’s poetry? How is existential anxiety manifested in Ibn Khafajah’s poem Al Jabal? What are his poetic strategies?